The Role of Wives as Breadwinners in Serang’s Traditional Markets in Enhancing Food Security - Luthfia, Chaula; Qotrun Nida; Marima Delmar Aldama; Windiyanti Bahari Putri (Journal of Judicial Review, 2024)
The institution of marriage inherently establishes reciprocal rights and responsibilities between husband and wife. Among these is the husband’s obligation to provide material and emotional support to his wife. Over time, societal changes have opened opportunities for women, including wives, to participate in earning a living, such as through their work in traditional markets. In this context, wives who engage in traditional market activities contribute significantly to meeting food needs and, consequently, to strengthening food security. This study seeks to elucidate the pivotal role played by wives who contribute to household income as key drivers of family food security. Furthermore, it evaluates the perspective of Law No. 18 of 2012 on Food regarding wives who engage in earning a livelihood as vendors in traditional markets. Utilizing a combination of field research and literature review, the study adopts a juridical-empirical and sociological approach. The findings highlight that wives working in traditional markets are instrumental in promoting food security. Their efforts extend beyond their own households to support local food systems. These women directly embody the four critical dimensions of food security: food availability, food accessibility, food utilization, and food stability. Their contributions underscore the essential role of female vendors in ensuring sustainable food security at both familial and community levels.